2016
DOI: 10.17523/bia.v73n4p272
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da silagem da rama da batata doce emurchecida e adicionada de fubá de milho como aditivo

Abstract: RESUMO: Objetivou-se investigar as características fermentativas e nutricionais da rama da batata doce (Ipomoea batatas) na forma de silagem utilizando níveis de fubá de milho como aditivo. O delineamento experimental utilizado foi inteiramente casualizado com sete níveis de aditivo (fubá de milho) (0; 5; 10; 15; 20; 25 e 30%) e quatro repetições, totalizando 28 mini silos laboratoriais (unidades experimentais). Efeito quadrático foi observado nos teores de matéria seca (MS), proteína bruta (PB), proteína inso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
2
Order By: Relevance
“…The highest crude protein contents were recorded at 15% CaO (Figure 3), attributed to the higher coating of sweet potato twigs by the particle film, which may be compared with the chlorophyll data. Despite the lower concentration of crude protein content in the control and in the 5 and 10% CaO treatments, it was observed that the obtained values remained above 7%, the minimum required for the maintenance of rumen microbiota (Van Soest, 1994), as also observed by Corrêa et al (2016) when evaluating silage from sweet potato branches. The application of the CaO particle film influenced the bromatological composition of sweet potato.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The highest crude protein contents were recorded at 15% CaO (Figure 3), attributed to the higher coating of sweet potato twigs by the particle film, which may be compared with the chlorophyll data. Despite the lower concentration of crude protein content in the control and in the 5 and 10% CaO treatments, it was observed that the obtained values remained above 7%, the minimum required for the maintenance of rumen microbiota (Van Soest, 1994), as also observed by Corrêa et al (2016) when evaluating silage from sweet potato branches. The application of the CaO particle film influenced the bromatological composition of sweet potato.…”
Section: Resultsmentioning
confidence: 76%
“…Sweet potato branches -due to their abundant aerial part, with a large number of succulent stems -are also an essential source of food for pigs that can be supplied as green fodder or silage (Monteiro et al, 2007;Corrêa et al, 2016). According to Aregheore (2004), some varieties of sweet potato have a potential of producing between 4.0 and 6.0 Mg ha -1 dry matter (DM), of which approximately 64% comprises the aerial part (leaves, petiole, and stem).…”
Section: Introductionmentioning
confidence: 99%
“…Para a produção de silagens, é importante que o teor de matéria seca da forragem esteja entre 25 e 30%, porém, frequentemente encontram-se nas ramas de batata-doce teores abaixo dessa faixa, sendo que uma forma de aumentar a matéria seca antes da ensilagem é o uso de aditivos, tornando uma alternativa para melhorar a qualidade final do material ensilado (Andrade Júnior et al, 2014;Corrêa et al, 2016).…”
Section: Matéria Seca Da Silagemunclassified
“…Os aditivos são utilizados para melhorar o processo fermentativo e a estabilidade aeróbica do produto final, diminuindo as perdas de MS. Além disso, são utilizados para aumentar o valor nutricional e a qualidade final da silagem (Antonio, 2016). Dentre esses aditivos se encontram o fubá de milho, farelo de trigo, e polpa cítrica onde irão agir elevando a MS da silagem, favorecendo uma boa fermentação (Corrêa, 2016;.…”
Section: Matéria Seca Da Silagemunclassified
“…Its rusticity guarantees resistance to drought, little demand on nutrients and advantageous competition with weeds, for quickly covering the soil. In addition, to use in human food, sweet potatoes can be used in animal feed and ethanol production (Corrêa et al, 2016;Silva, Almeida, Alvim-Ferraz, & Dias, 2018;Suparno, Prabawardani, & Pattikawa, 2016;Vizzotto, Pereira, Castro, Raphaelli, & Krolow, 2017).…”
Section: Introductionmentioning
confidence: 99%